Preliminary studies on Sirex noctilio (Hymenoptera-Siricidae) in pine plantations in the Calamuchita Valley, Córdoba, Argentina - López, Adlih; Demaestri, Marcela; Zupan, Esteban; Barotto, Omar (Bosque (Valdivia), 2002)
In 1994, the wood wasp parasite Sirex noctilio was identified in Pinus spp. growing in the Calamuchita Valley of Cordoba, Argentina. This insect causes direct and indirect damage to trees, eventually causing death. The larval activity consisting of feeding and injecting a phytotoxic mucus, coincides with infection of the symbiotic pathogenic fungus Amilostereum areolatum. The "pine borer wasp" has a commercial impact, since the export of infested pinewood is prohibited by international agreement, thus affecting the regional economy based on pine forest products. A research project at the Universidad Nacional de Rio Cuarto dealing with the prevalence, distribution and incidence of Sirex in the region was begun in 1996. We are also studying the bioecology and natural enemies of the insect, as well as the convenience of introducing a parasite nematode, Deladenus sincidicola, to try to managing the problem. The "pine borer wasp" was declared an agricultural pest for the Province of Cordoba in 1997.